Workplace Training as a Social Practice: How Trainers Experience the Structural Dynamics of German Apprenticeship - Bahl, Anke [Verfasser] (My University, 2019)
"Since learning opportunities in the workplace depend on both the organisation of work and good relationships, growing attention in the global skills debate is given to the role and contribution of formal and informal in-company trainers. How to raise the attractiveness of their job and enhance their competences to meet changing labour market demands have become major issues of concern. In spite of many initiatives and projects targeted at the professionalization of this heterogeneous group by educational policy, however, not much progress seems to have been made. In Germany at least, VET providers offering a diversity of newly developed training schemes below and above the long established standard of the trainer aptitude regulation suffer from a lack of demand. This paper suggests that one of the deficits of VET policy lies in its restricted conception of trainers as individual agents and educators. It obstructs the recognition of trainers' achievements within often restricted organisational conditions of training in an economic setting. These circumstances have an essential impact on the daily practice of in-company trainers but are usually neglected by both educational research and policy. Inspired by ethnographic research in German companies, the presentation will shed light on the inner dynamics of the training task and suggest to view it less as an educational but a social practice. To find reasons for the striking discrepancy between policy and practice, a BIBB research project was launched in the period between 2009 and 2012. It followed a qualitative methodology and focused on "The situation of apprenticeship trainers in companies". In the course of 14 case studies altogether 127 interviews with various types of trainers, HR managers, executives, employee representatives and apprentices in small, medium and large enterprises of varying sectors were collected. Professional development of workplace trainers requires as a starting point the systematic reflection of their role within the company context. Strengthened awareness and self-esteem in their role as learning facilitators are prerequisites for the development of personal strategies to negotiate their contradictory demands. Furthermore, learning in the workplace needs to be promoted as a concept that entails more than insular situations of instruction but requires a supportive and comprehensive strategy for the organisation as a whole." (excerpt; BIBB-Doku)
Keywords: P 3.2.1 Ausbilder; S 3.2 Unternehmen und Behörden; Betriebliche Berufsausbildung; Ausbilder; Professionalisierung; Berufliches Selbstverständnis; Berufliche Sozialisation; Organisationsstruktur; Lernen am Arbeitsplatz